Psychological consequences of wife abuse (2004)
"The present study represents an attempt at contributing to literature by addressing an under researched topic of considerable health concern. The study investigated the psychological consequences of wife abuse in three high density residential areas' in Ibadan North Local Government Area of Ibadan. Four hundred and eighty women who were visited at home by the researchers participated in the study. Participants' mean age was 35.4 years with a standard deviation of 6.27. Interviews were conducted for participants, using standard and widely used measures of depression, self-esteem and wife abuse. Results indicated that all the participants reported at least some forms of spousal abuse. However, women who reported severe abuse were significantly higher on the depression measure, t(2,478)=-to.22;P<.01 than those who reported mild abuse. Results also showed that old abused women scored significantly lower on depression than young abused women, F(1,337)=P<.01. Likewise, high education abused women self reported significantly higher on depression than low education abused women, t(2,337)= 5.44. On self-esteem, old abused women were significantly higher than their young abused counterparts, t(2,337)=P<.05. Educational status also had significant effect on self-esteem, t(2,337)=7. 10, with low education women scoring significantly higher on self-esteem than high education women. The implication of this is that wife abuse negatively impact on abused women's self-esteem and depression, and that the effect is more on young, highly educated women than young less educated women. The need for concerted effort in campaigns and enlightenment programmes aimed at empowering women and making perpetrators of wife abuse realise why the act should be stopped was highlighted. "